The journey of cardosin A in young Arabidopsis seedlings leads to evidence of a Golgi-independent pathway to the protein storage vacuole - Pereira, Cláudia; Vieira, Vanessa; Pissarra, José; Pereira, Susana (Frontiers in Plant Science, 2023)
The aspartic proteinase cardosin A is a vacuolar enzyme found to accumulate in protein storage and lytic vacuoles in the flowers and protein bodies in the seeds of the native plant cardoon. Cardosin A was first isolated several decades ago and has since been extensively characterized, both in terms of tissue distribution and enzyme biochemistry. In the native system, several roles have been attributed to cardosin A, such as reproduction, reserve mobilization, and membrane remodeling. To participate in such diverse events, cardosin A must accumulate and travel to different compartments within the cell: protein storage vacuoles, lytic vacuoles, and the cytoplasmic membrane (and eventually outside the cell). Several studies have approached the expression of cardosin A in Arabidopsis thaliana and Nicotiana tabacum with promising results for the use of these systems to study of cardosin A trafficking. A poly-sorting mechanism has been uncovered for this protein, as two different vacuolar sorting determinants, mediating different vacuolar routes, have been described. The first is a conventional C-terminal domain, which delivers the protein to the vacuole via the Golgi, and the second is a more unconventional signal—the plant-specific insert (PSI)—that mediates a Golgi-independent route. The hypothesis that these two signals are activated according to cell needs and in organs with high metabolic activity is investigated here. An Arabidopsis line expressing cardosin A under an inducible promoter was used to understand the dynamics of cardosin A regarding vacuolar accumulation during seed germination events. Using antibodies against different regions of the protein and combining them with immunofluorescence and immunocytochemistry assays in different young seedling tissues, cardosin A was detected along the secretory pathway to the protein storage vacuole, often associated with the endoplasmic reticulum. More interestingly, upon treatment with the drug Brefeldin A, cardosin A was still detected in protein storage vacuoles, indicating that the intact protein can bypass the Golgi in this system, contrary to what was observed in N. tabacum. This study is a good starting point for further research involving the use of fluorescent fusions and exploring in more detail the relationship between cardosin A trafficking and plant development.